2015
DOI: 10.4081/hpr.2015.2115
|View full text |Cite
|
Sign up to set email alerts
|

Overview of attention deficit hyperactivity disorder in young children

Abstract: Attention deficit hyperactivity disorder (ADHD) is a complex disorder, which can be seen as a disorder of life time, developing in preschool years and manifesting symptoms (full and/or partial) throughout the adulthood; therefore, it is not surprising that there are no simple solutions. The aim of this paper is to provide a short and concise review which can be used to inform affected children and adults; family members of affected children and adults, and other medical, paramedical, non-medical, and education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 196 publications
1
56
1
4
Order By: Relevance
“…In the present study, in which, for the first time, eye-tracking was used to record eye movement latency in children with ADHD, we reported significant longer latency for children with ADHD only in the endogenous condition for the invalid sub-condition when compared to TD children. Our result reinforced previous findings, suggesting that children with ADHD have difficulties to voluntarily disengage their attention from an erroneous condition (invalid condition) in order to engage attention in the correct direction ( 31 , 32 ). Recently, in an fMRI study exploring the Posner task performance in 11 healthy adults, Meyer et al ( 33 ) showed that during the endogenous condition and invalid sub-condition, the cerebellar frontal activity of the left hemisphere was greater with respect to valid sub-condition.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, in which, for the first time, eye-tracking was used to record eye movement latency in children with ADHD, we reported significant longer latency for children with ADHD only in the endogenous condition for the invalid sub-condition when compared to TD children. Our result reinforced previous findings, suggesting that children with ADHD have difficulties to voluntarily disengage their attention from an erroneous condition (invalid condition) in order to engage attention in the correct direction ( 31 , 32 ). Recently, in an fMRI study exploring the Posner task performance in 11 healthy adults, Meyer et al ( 33 ) showed that during the endogenous condition and invalid sub-condition, the cerebellar frontal activity of the left hemisphere was greater with respect to valid sub-condition.…”
Section: Discussionsupporting
confidence: 92%
“…Since learning difficulties and reduced academic achievement among children with attention deficits are well-known [1, 33], a potential association between maternal diabetes and attention deficits in the offspring is plausible and has been suggested in previous studies [811]. However, this was not supported by the findings of the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…Structural and functional abnormalities in cerebellum and basal ganglia have further been associated with motor impairments 43 , which are frequent in nearly half of ADHD cases 44 . Other areas identified through our eQTL analysis have also been related to ADHD, for instance: i) Remarkable differences in the shapes of caudate-putamen basal ganglia and smaller volumes have been reported in ADHD boys in comparison to typically developing individuals [45][46][47][48] ; ii) in adult males with ADHD, right caudate volume correlates with poor accuracy on sensory selection tasks 49 and also with hyperactivity/impulsivity 50,51 ; iii) nucleus accumbens is one of the areas, together with the caudate nucleus, putamen, amygdala, and hippocampus, reported to be structurally altered in the brain of ADHD patients 52 . A delayed cortical development e.g.…”
Section: Artn C2orf82 and Pidd1 (Figs 2 To 4 Andmentioning
confidence: 99%